A Review of Violence Risk Assessment for Mentally Disordered Patients in Mainland of China. (December 2014) - Gu, Yan; Singh, Jay P.; Yun, Libing; Hu, Zeqing
The Chinese research literature on violence risk assessment is small compared with Western countries. However, violence by mentally disordered populations is an area of considerable importance in China, given major legal developments in recent years. The aim of the present article was to provide an overview of the current state of violence risk assessment practices in China, focusing on the role that such assessments play in forensic and non-forensic hospitals as well as in community treatment settings. The Chinese evidence base on currently available approaches to violence risk assessment was also explored. Further research on risk assessment, formulation, communication, and management is needed before it can be argued that practitioners in China charged with making risk-based decisions are using the most scientifically defensible procedures.